Between Control and Empowerment: Local Government and Acknowledgement of Adat Villages in Indonesia - Suartina, Tine (UI Scholars Hub, 2020)
The local government’s acknowledgment of adat (customary) communities and adat villages, as regulated in the Village Law 6/2014 , appear to signal an increasing recognition of adat law. However, the current acknowledgment practices and adat village formalizations have become areas of legal contestation between adat communities and state-national and local governments. Despite the resurgence of formal legal pluralism, those acknowledgment and accommodation mechanisms are double-edged. They involve control and empowerment as emphasized in Hellman’s framework applied to analyze the dilemma in a plural society regarding cultural politics. On the one hand, the acknowledgment and accommodation mechanisms conducted through an official process necessitate the fulfillment of a list of requirements set by the government (controlled). Thus, there is a possible drawback for an asymmetrical position between the formal institution (recognition giver) and the community (recognition recipient). Conversely, the mechanisms are used by adat communities as a means to gain the rights of self-determination. Thus, empowerment is realized, because most local acknowledgment regulations include obligations of protection by the state and local governments. This paper discusses the dynamics of legal pluralism in Indonesia using cases of local acknowledgment and adat village institutionalization in which adat law becomes an element in formalizing the communities’ existence and adat village format. However, a question remains regarding whether the central position of adat law in such a mechanism is merely applied to fulfill the acknowledgment and accommodation requirement or whether it actually strengthens its capacity.